Anaerobic Codigestion of Grass and Sewage Sludge: Laboratory Experiments and Feasibility Analysis. (1st November 2016) - Hidaka, Taira; Wang, Feng; Sakurai, Kensuke; Tsumori, Jun; Minamiyama, Mizuhiko
ABSTRACT: : Grass is drawing attention for its high potential for biogas production. Anaerobic digesters in wastewater treatment plants can be used for producing biogas by processing grass without having to invest in the construction of new treatment facilities. Batch and continuous digestion experiments were conducted to assess the feasibility of codigestion of sewage sludge and grass. The focus was on a thermophilic condition, starting‐up from existing mesophilic anaerobic digestion of sewage sludge only. The batch and continuous experiments used two different sewage sludges. Results demonstrated a methane generation of approximately 0.2 normal liter‐methane/g volatile solids‐grass. The addition of grass did not affect the ammonia concentration and improved the dewaterability of the digested sludge. The start‐up performance from mesophilic digested sewage sludge to thermophilic codigestion with grass was confirmed. A feasibility analysis demonstrated that codigestion is applicable in terms of energy recovery and greenhouse gas emission, depending on the transport distance of grass.